PEMBERDAYAAN LITERASI FINANSIAL MASYARAKAT DI KELURAHAN TUOY KECAMATAN UNAAHA KABUPATEN KONAWE - Rostin Rostin; Heppi Millia; Muh. Yani Balaka; Irmawati P. Tamburaka; Ambo Wonua Nusantara; Asrif Putra (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aims to enhance the financial literacy knowledge and skills of residents in Tuoy Subdistrict, Unaaha District, Konawe Regency. Financial literacy is essential for individuals to manage their finances effectively and avoid issues such as illegal online loans, loan sharks, and poor household cash flow management. The activity was carried out through lectures and interactive question-and-answer sessions involving local government staff, housewives, MSME actors, cooperative managers, and the general community. The materials covered basic financial literacy concepts, financial planning, debt management, introduction to formal financial institutions, and risks in digital financial transactions. The results show an improvement in participants’ understanding, reflected in their active participation, ability to identify financial problems, and commitment to applying better financial management practices. This program supports government and Financial Services Authority (OJK) efforts to build a financially literate society capable of responsibly utilizing financial products and services.